PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN STUDI PADA RUMAH SAKIT TELOGOREJO SEMARANG (Students' Journal of Economic and Management, 2016)
This study analyzed the influence of leadership style, employee motivation and job satisfaction on employee performance Telogorejo Hospital Semarang. Sampling technique in this research were 100 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing questionnaires to the respondents in order to obtain information. The research objective formulated to determine the effect of leadership style, employee motivation and job satisfaction on employee performance Telogorejo Hospital Semarang. Data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of each independent variable in the regression analysis test. The results of the research are: (1) leadership style has a positive and significant impact on employee performance Telogorejo Hospital Semarang. (2) motivation to work has a positive and significant impact on employee performance Telogorejo Hospital Semarang. (3) job satisfaction has a positive influence on employee performance dn significant Telogorejo Hospital Semarang Keywords: leadership style, employee motivation, job satisfaction and employee performance